2016
DOI: 10.1016/j.athoracsur.2015.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Use and Outcomes of Minimally Invasive Lobectomy for Stage I Non-Small Cell Lung Cancer in the National Cancer Data Base

Abstract: Background Previous studies have raised concerns that video-assisted thoracoscopic (VATS) lobectomy may compromise nodal evaluation. The advantages or limitations of robotic lobectomy have not been thoroughly evaluated. Methods Perioperative outcomes and survival of patients who underwent open versus minimally-invasive surgery (MIS [VATS and robotic]) lobectomy and VATS versus robotic lobectomy for clinical T1-2, N0 non-small cell lung cancer from 2010 to 2012 in the National Cancer Data Base were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(106 citation statements)
references
References 16 publications
(21 reference statements)
5
98
2
1
Order By: Relevance
“…1,15 Minimally invasive video-assisted thoracoscopic surgery (VATS) and, more recently, robot-assisted VATS (da Vinci Surgical System, Intuitive Surgical Inc.) for various intrathoracic procedures, particularly pulmonary lobectomy for lung malignancy, have been unequivocally shown to be superior to open thoracotomy with a significant reduction in postoperative morbidity, mortality, and length of stay, translating into increased cost-effectiveness with similar oncological outcomes. 26 Robotic endoscopic surgery has been widely and successfully adopted by many subspecialties. By virtue of the multiple operating angles of its 4 dexterous robotic arms, 10× optical magnification, and 3D high-resolution imaging, the da Vinci Surgical System allows the surgeon to perform precise dissections from extreme angles, even for a deep target or within a narrow space.…”
mentioning
confidence: 99%
“…1,15 Minimally invasive video-assisted thoracoscopic surgery (VATS) and, more recently, robot-assisted VATS (da Vinci Surgical System, Intuitive Surgical Inc.) for various intrathoracic procedures, particularly pulmonary lobectomy for lung malignancy, have been unequivocally shown to be superior to open thoracotomy with a significant reduction in postoperative morbidity, mortality, and length of stay, translating into increased cost-effectiveness with similar oncological outcomes. 26 Robotic endoscopic surgery has been widely and successfully adopted by many subspecialties. By virtue of the multiple operating angles of its 4 dexterous robotic arms, 10× optical magnification, and 3D high-resolution imaging, the da Vinci Surgical System allows the surgeon to perform precise dissections from extreme angles, even for a deep target or within a narrow space.…”
mentioning
confidence: 99%
“…Evaluating 8,253 RATS lobectomies in the Healthcare Cost and Utilization Project National Inpatient Sample, Tchouta et al found that high-volume centers had a shorter LOS and decreased mortality (15). Yang et al evaluated 30,040 lobectomies for stage I lung carcinoma (7,824 VATS and 2,025 RATS) in the National Cancer Database and found that MIS approaches were associated with increased 30-day readmission but shorter LOS and improved 2-year survival (16).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term overall and disease-free survival, however, have not been reported by these studies. Other studies have demonstrated no significant difference in upstaging between the two techniques (18)(19)(20). (23)(24)(25)(26).…”
Section: Vatsmentioning
confidence: 99%